2016
DOI: 10.1111/tme.12303
|View full text |Cite
|
Sign up to set email alerts
|

Blood donation in Guangdong Province, China, from 2006–2014

Abstract: With nearly a decade of efforts, blood donation in Guangdong has developed rapidly and sustainably. All blood collection and supply institutions must strengthen efforts to improve awareness of blood donation among the population, retain repeat and regular donors and reduce the rate of FRMBD in favor of the development of VNRBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…10 In Guangdong Province, China, however, where blood donations increased by nearly 40% between 2006 and 2014, the proportion of FRD had decreased from 40% to 20%. 11 We can find no recent information from the Pacific region about trends in blood donor status during the last 5 years to compare with our findings. …”
Section: Discussionmentioning
confidence: 42%
“…10 In Guangdong Province, China, however, where blood donations increased by nearly 40% between 2006 and 2014, the proportion of FRD had decreased from 40% to 20%. 11 We can find no recent information from the Pacific region about trends in blood donor status during the last 5 years to compare with our findings. …”
Section: Discussionmentioning
confidence: 42%
“…One study reported numbers of volunteer blood donations in Guangdong province, among the most developed provinces, increased 38% from 2006 to 2014, whereas blood donations from relatives decreased by one-half and platelet donations by two-thirds. 59 Efforts to increase blood donations are underway, and better donor education is greatly needed. Eliminating paid blood donation is important to control infection risk to donors and recipients in view of prior outbreaks of hepatitis-B and hepatitis-C viruses and HIV in Chinese paid blood and plasma donors.…”
Section: Infection Control Blood Products and Protocol-based Therapymentioning
confidence: 99%